Glandular trichomes, essential oil composition, anti-Aspergillus and antioxidative activities of Lamium purpureum L. ethanolic extracts - Grujić, Slavica M.; Savković, Željko D.; Ristić, Mihailo S.; Džamić, Ana M.; Ljaljević Grbić, Milica V.; Vukojević, Jelena B.; Marin, Petar D. (Archives of Biological Sciences, 2020)
Paper description: Lamium purpureum L. (Lamiaceae) glandular trichomes and the composition of essential oil were analyzed. Two types of trichomes, non-glandular and glandular (peltate and capitate) were identified. The main compounds of essential oil were trans-anethole (59.61%), fenchone (6.54%), α-pinene (6.14%) and β-pinene (4.98%). The antioxidant activities of the ethanolic plant extracts were determined using DPPH, ABTS, FRAP and TRP assays. Antifungal activity of the ethanolic extract was observed, While the extracts did not exhibit fungicidal activity, morphophysiological changes (sporulation loss, depigmentation of conidial heads) were observed in all tested isolates. L. purpureum could be a new potential source of natural antioxidants. Abstract: The aim of this study was to investigate the structure of glandular trichomes and essential oil composition of Lamium purpureum L. (Lamiaceae) and to determine potential biological activities of its different extracts. The micromorphology and distribution of trichomes on vegetative plant parts were investigated using scanning electron microscopy (SEM). Two types of trichomes were identified: non-glandular (simple, uniseriate, multicellular) and glandular (both peltate and capitate). The essential oil of L. purpureum was isolated by hydrodistillation and analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). The main compounds were trans-anethole (59.61%), fenchone (6.54%), α-pinene (6.14%) and β-pinene (4.98%). The total phenol and flavonoid contents of 10%, 30% and 50% ethanol extracts were determined spectrophotometrically. The free radical scavenging and reducing power activity of extracts were analyzed using the DPPH and ABTS radical scavenging methods, and the ferric reducing antioxidant power (FRAP) and total reducing power (TRP) assays. The 50% ethanolic extract exhibited the strongest antioxidative activity while the lowest was determined for the 10% ethanolic extract. Antifungal activity of L. purpureum hydroalcoholic extracts was evaluated against eight Aspergillus species by the microdilution method. Light microscopy (LM) demonstrated structural abnormalities of the tested Aspergilli. While the plant extracts did not exhibit fungicidal activity, morphophysiological changes (sporulation loss and depigmentation of conidial heads) were observed in all tested isolates. https://doi.org/10.2298/ABS200117019G Received: January 17, 2020; Revised: February 25; Accepted: April 7, 2020; Published online: April 23, 2020 How to cite this article: Grujić SM, Savković ŽD, Ristić MS, Džamić AM, Ljaljević Grbić MV, Vukojević JB, MarinPD. Glandular trichomes, essential oil composition, anti-Aspergillus and antioxidative activities of Lamium purpureum L. ethanolic extracts. Arch Biol Sci. 2020;72(2):253-63.